The 'help' question doesn't help when screening for major depression: external validation of the three-question screening test for primary care patients managed for physical complaints - Verdon François (BMC Medicine, 2011)
Abstract Background Major depression, although frequent in primary care, is commonly hidden behind multiple physical complaints that are often the first and only reason for patient consultation. Major depression can be screened by two validated questions that are easier to use in primary care than the full Diagnostic and Statistical Manual of Mental Disorders, fourth edition (DSM-IV) criteria. A third question, called the 'help' question, improves the specificity without apparently decreasing the sensitivity of this screening procedure. We validated the abbreviated screening procedure for major depression with and without the 'help' question in primary care patients managed for a physical complaint. Methods This diagnostic accuracy study used data from the SODA (for 'SOmatisation Depression Anxiety') cohort study conducted by 24 general practitioners (GPs) in western Switzerland that included patients over 18 years of age with at least a single physical complaint at index consultation. Major depression was identified with the full Patient Health Questionnaire. GPs were asked to screen patients for major depression with the three screening questions 1 year after inclusion. Results Of 937 patients with at least a single physical complaint, 751 were eligible 1 year after index consultation. Major depression was diagnosed in 69/724 (9.5%) patients. The sensitivity and specificity of the two-question method alone were 91.3% (95% CI 81.4 to 96.4) and 65.0% (95% CI 61.2 to 68.6), respectively. Adding the 'help' question decreased the sensitivity (59.4%; 95% CI 47.0 to 70.9) but improved the specificity (88.2%; 95% CI 85.4 to 90.5) of the three-question method. Conclusions The use of two screening questions for major depression was associated with high sensitivity and low specificity in primary care patients presenting a physical complaint. Adding the 'help' question improved the specificity but clearly decreased the sensitivity; when using the 'help' question, four out of ten patients with depression will be missed, compared to only one out of ten with the two-question method. Therefore, the 'help' question is not useful as a screening question, but may help discussing management strategies.